2021
DOI: 10.25115/ejrep.v19i53.3871
|View full text |Cite
|
Sign up to set email alerts
|

Connections between Teachers’ Motivational Behaviour and School Student Engagement

Abstract: Introduction.  Teachers are invited to seek answers to many questions on their professional growth path. This article aims at drawing attention to their motivational behaviour in teaching school students. According to the theory of self-determination, appropriate motivating (that is, autonomy-supportive) behaviour of teachers can respond to a child’s essential psychological needs, and thus enable him or her to engage in the teaching and learning process. Therefore, the goal of this study is to examine the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(57 reference statements)
0
9
0
2
Order By: Relevance
“…Our results show that boys' behavioural engagement means are statistically lower in comparison with girls. Such a tendency is noticed by many scientists [13][14][15][16][17]52,60]. It is clear that a variety of factors in the learning environment can be relevant to students' engagement.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results show that boys' behavioural engagement means are statistically lower in comparison with girls. Such a tendency is noticed by many scientists [13][14][15][16][17]52,60]. It is clear that a variety of factors in the learning environment can be relevant to students' engagement.…”
Section: Discussionmentioning
confidence: 95%
“…As stated by Tomaszewski et al [19], low SES students show lower levels of engagement than other students and the effects of SES on achievement are partially mediated through student engagement. Comparing student engagement in terms of gender, a difference was also found-male students of different ages showed a tendency towards lower engagement [13][14][15][16][17]. For instance, Oga-Baldwin and Nakata found that male students showed a tendency towards lower engagement, lower internally regulated motives, and higher externally regulated motives [14].…”
Section: Theoretical Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…Si bien el ejercicio de la docencia es un proceso complejo, el profesor, con la autoridad que recae en él, tiene la capacidad para empoderar o confundir a sus estudiantes (Brandisauskiene et al,, 2021); por ello, según Arbaugh (2010), tanto su presencia como su comportamiento pueden ser predictores de los resultados de aprendizaje. Desde otro ángulo, Mahmoodi et al, (2021) comentan que los profesores que valoran el conocimiento y el desarrollo de habilidades estarán más interesados en aplicar un estilo centrado en el estudiante para que este último también desarrolle sus habilidades y conocimientos.…”
unclassified
“…Por su parte, Astudillo y Chévez (2021) destacan que un docente facilitador, creativo y acompañante puede animar a sus estudiantes a seguir sus clases en la modalidad sincrónica, generando espacios retadores, motivantes y contextualizados que fomenten el aprendizaje. Se ha reportado que la motivación de los estudiantes disminuye cuando reciben retroalimentación negativa, lo que a su vez puede llevar a cuadros de depresión (Thompson et al,, 2021); adicionalmente, se ha visto que el perfil motivacional del docente predice el compromiso de los estudiantes (Brandisauskiene et al,, 2021).…”
unclassified